FACTORS INFLUENCING THE PERCEPTION OF LEISURE AND RECREATIONAL TOURISM DESTINATIONS IN SOUTH INDIA - D., Bharath Kumar; M., Thyagaraju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the factors influencing the perception of leisure and recreational tourism destinations in South India, aiming to identify key elements that affect tourists’ evaluations and experiences. Utilizing a comprehensive review of current literature and empirical research, the study highlights several critical factors that shape tourist perceptions: infrastructure and accessibility, safety & security, hospitality and service quality, entertainment and leisure activities, social and environmental impact. The research synthesizes findings from various studies to present a holistic view of how these factors interact to impact overall destination appeal. Natural beauty and cultural heritage are identified as primary drivers of positive perceptions, while perception of tourist factors is significantly affecting tourist satisfaction. The results provide valuable insights for tourist’s perception on destinations.